Complete Genomic Sequence of Duck Flavivirus from China - Liu, Ming (American Society for Microbiology, 2012)
We report here the complete genomic sequence of the Chinese duck flavivirus TA strain. This work is the first to document the complete genomic sequence of this previously unknown duck flavivirus strain. The sequence will help further relevant epidemiological studies and extend our general knowledge of flaviviruses.